Assessment of Groundwater Quality for Irrigation in Jhagadia, Netrang and Valia Taluka of Bharuch District in South Gujarat, India - , Patil, L. M., Patel, K. G., Naik, V. R., Valvi, V. I. (Archives of Current Research International, 2024)
Bharuch, a heavily industrialized district on the west coast, faces challenges like over-extraction and contamination, which threaten its groundwater quality. In response, a post-monsoon 2023 assessment was conducted in the Jhagadia, Netrang, and Valia talukas, where water samples from 78 locations were collected and analyzed. These locations were identified using landforms developed through GIS. The study found that around 40% of the TGA in these blocks is used for agriculture, with 52,106 hectares for single crops and 7,843 hectares for double crops, making up 15.05% of the total cultivated area. Eastern part of Jhagadia and Netrang recorded deep water levels (10–20 m), while other areas had moderately shallow levels (5–10 m). Tube wells were mainly found in Valia, northern Jhagadia, and western Netrang, whereas dug wells dominated eastern Netrang and southeastern Jhagadia. Irrigation water pH ranged from 6.31 to 8.82, averaging 6.97, with higher pH in Jhagadia. Electrical conductivity (EC) was highest in Valia (0.66–2.94 dSm⁻¹), and medium salinity was noted in Jhagadia (1.03 dSm⁻¹) and Netrang (0.71 dSm⁻¹), affecting irrigation suitability. All samples had a SAR classification of S1 (<10). Most water samples were "Suitable" based on RSC, except some in Valia with RSC >1.25 meL⁻¹. Chloride levels varied from 0.50 mg/L-1 to 25.48 mg/L-1. The specific soil management practices, such as gypsum application, improving drainage and the growing of salt-tolerant crop varieties can help mitigate potential negative impacts on crop productivity.